Prai Ijing: Dissecting the Magic of Community-Based Tourism in the Heart of West Sumba - LEDEWARA, Kornelia Esyi; PRANOTO, Pranoto (Journal of Tourism Economics and Policy, 2025)
The purpose of this study was to identify the analysis of the effectiveness of the application of the Community Based Tourism concept in Prai Ijing Traditional Village, West Sumba Regency. The method used was field studies and direct interviews with various respondents or related parties, such as local communities, tourism destination managers and tourists. The data collected were analyzed using qualitative and interpretive approaches. The results of the study showed that the application of the CBT concept has provided many benefits, such as increasing local community income, increasing local community awareness of the importance of maintaining the environment, culture and local wisdom, increasing the quality of tourist experience, and increasing the promotion and image of tourist destinations. However, the application of the CBT concept also has challenges, such as the lack of understanding and skills of local communities in terms of tourism management and promotion. This can be done by providing training and assistance to local communities so that they can better understand and work together in managing tourism well between local communities, tourism destination managers, and local governments in an effort to develop and promote sustainable tourist destinations.